Simulation Of Rectangular Patch Microstrip Antenna For Wimax At 3.5 GHz Frequency - Muhammad Iqbal; Aprima A Matondang; Stephanie Pardede; The Fitri Astarani; Morlan Pardede (Institute of Computer Science (IOCS), 2026)
Microstrip antenna is one of the compact antenna types that can be implemented using PCB material and consists of three main parts, namely the radiating element, substrate, and ground plane. This antenna is widely used in wireless communication systems because it has a simple structure, small size, and is easy to integrate with electronic devices. One of its applications is in WiMAX systems operating at 3.5 GHz to support more efficient data transmission. In this study, a rectangular patch microstrip antenna was designed as an alternative antenna for WiMAX systems. The design process was carried out using AWR software to obtain antenna characteristics that meet the required specifications. The evaluated performance parameters included return loss, VSWR, and bandwidth. Based on the simulation results, the designed antenna achieved a return loss of -14.21 dB, a VSWR of 1.484, and a bandwidth of 152 MHz. After optimization, the final design achieved an improved return loss of -26.93 dB and a VSWR of 1.09. These results indicate that the proposed antenna has good performance and is suitable for supporting WiMAX communication systems